The Role of Mediation Agreement of Divorce Which Ended Amicably (Case at Yogyakarta Religious Court) - Muhammad, Dodi; Sanjaya, Umar Haris (Universitas Muhammadiyah Surabaya, 2022)
Mediation is one form of alternative dispute resolution outside the Court. The purpose of mediation is to resolve disputes between the parties by involving a neutral and impartial third party. The process of implementing mediation is actually very simple, but in reality there are many things that hinder or complicate the success of mediation. It is proven from the number of unsuccessful mediations compared to successful mediations in court. The formulation of the problem proposed is: How is the consideration of the divorce mediation peace agreement at the Yogyakarta Religious Court and whether the divorce dispute mediation agreement is in accordance with Supreme Court Regulation (Perma) No. 1 of 2016. The purpose of this research is to find out how the consideration of the peace agreement on divorce mediation in the Yogyakarta Religious Court and to find out the divorce mediation agreement according to Perma No. 1/2016. 1 of 2016. This research includes Empirical Research. Research data were collected by means of interviews and literature study. The analysis was carried out by Sociological Jurisdiction. The results of the analysis at the Yogyakarta Religious Court in 2017 mediation succeeded in reaching an agreement that only 11 cases out of a total of 241 cases were mediated, in 2018 only 19 cases out of a total of 265 cases, in 2019 only 23 cases out of a total of 204 cases, and in 2020 only 16 cases out of a total of 191 cases. Consideration of peaceful mediation, namely the role of the mediator and the good faith of the parties in conducting mediation. 1 of 2016, such as the type of case requiring mediation, good faith in taking mediation, costs incurred in mediation, mediation venue, and mediator certification. This makes mediation successful/peaceful, peace is one of the goals in civil disputes.Â